Respuesta :

Answer:

Subtract 4 from both sides.

Step-by-step explanation:

So we have the equation:

[tex]4-3(x+6)=28[/tex]

The very first step we should take is to subtract 4 from both sides. In fact, this is the only step we can take (without complicating things). So:

[tex](4-3(x+6))-4=(28)-4[/tex]

The left side cancels. Subtract on the right:

[tex]-3(x+6)=24[/tex]

To solve, divide both sides by -3:

[tex]x+6=-8[/tex]

Now, subtract 6 from both sides. So:

[tex]x=-14[/tex]

The value of x would be -14.

ACCESS MORE